1997
DOI: 10.1016/s0376-7388(96)00204-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gelation conditions on gas separation performance for asymmetric polysulfone membranes

Abstract: Effect of gelation conditions on gas separation performance for asymmetric polysulfone membranes Yamasaki, A.; Tyagi, R. K.; Fouda, A. E.; Matsuura, T.; Jonasson, K. Received 7 December 1995; revised 4 July 1996; accepted 5 July 1996 Abstract Asymmetric gas separation membranes were prepared by the phase inversion technique under different gelation conditions from polysulfone/N,N-dimethylacetamide (DMAc) solutions. The dual bath method was employed to control the skin layer properties: the cast film was immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…Thus, during the S‐N exchange process in the coagulation bath, the P/S/N mixture stays in the enlarged miscible region for a longer period, allowing formation of a thicker skin layer with fewer defects. Yamasaki et al2 and Lee et al3 used isopropanol, instead of water, as the first nonsolvent in their membrane fabrication by the dry‐wet phase inversion method. The membrane was then transferred into water, the second nonsolvent, to complete the phase separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, during the S‐N exchange process in the coagulation bath, the P/S/N mixture stays in the enlarged miscible region for a longer period, allowing formation of a thicker skin layer with fewer defects. Yamasaki et al2 and Lee et al3 used isopropanol, instead of water, as the first nonsolvent in their membrane fabrication by the dry‐wet phase inversion method. The membrane was then transferred into water, the second nonsolvent, to complete the phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, the skin layer thickness, and consequently the selectivity, increased while the flux decreased with an increase in the period of immersion in isopropanol. Despite a significant improvement in reducing the number of defects, Yamasaki et al2 reported that further lamination by silicone rubber was still necessary to stop the leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane casted from a dilute polymer solution produces a thin and porous selective layer that promotes high value of permeance but low selectivity. In contrast, higher polymer concentration in polymer solution leads to a denser and thicker selective layer that promotes higher selectivity but lower permeance [28,29]. Interaction of solvent-polymer and nonsolvent-polymer can increase with increasing polymer concentration.…”
Section: Polymer Concentrationmentioning
confidence: 99%
“…The results indicate that the phase separation and vitrification processes occurring during the wet process should be as rapid as possible. Another study was held by Yamasaki et al [29] using dual bath method. The first gelation media is 2-propanol and the second gelation media is water.…”
Section: Influence Of Gelation Medium and Conditionsmentioning
confidence: 99%
“…It is generally believed that for the PDMS coating gas separation membranes, the PDMS layer was used to plug up the defects in the dense skin layer of PSF membrane and force the gas to permeate through the polymer matrix in the skin layer. The membrane morphology was determined by the phase separation process, and the structure of the skin layer decided the gas separation performance [17][18][19]. The extension of the evaporation time could make the skin layer denser and thicker, leading to the increase of the gas permeating resistance and the drop of the flux.…”
Section: Performance Of the Pdms/psf Complex Membranesmentioning
confidence: 99%